KEMAMPUAN Flavobacterium sp NUB1 DALAM MENGGUNAKAN ALIFATIK NITRIL UNTUK PERTUMBUHANNYA - Nunik Sulistinah (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
A bacteria isolate capable utilizing 1% (v/v) acetonitrile and butironitrile as thesolesource of carbon and nitrogen was isolated from industrial effluents ofPTPetrokimia-Gresik and identified as Flavobacterium sp NUB1. The bacteriaisolatewas able to grow in both acetonitrile and butironitrile at concentrationofup to 4% (v/v). The highest growth was reached at 1% concentration ofacetonitrileand butironitrile, but the bacteria isolate was not able to grow onacrilonitrile.The specific growth rate (Î¼) of the isolate was 0,029 h-1. Themajorobjective of this study was to explore the abilities of the isolate to utilizesomealiphatic nitriles and then further evaluate the metabolite product of thenitriledegradation.Key words: aliphatic nitrile, biodegradation, Flavobacterium sp. NUB1